Adapting the Group Lifestyle Balance™ Program for Weight Management Within a Large Health Care System Diabetes Education Program. (May 2014) - Greenwood, Deborah A.; Kramer, M. Kaye; Hankins, Andrea I.; Parise, Carol A.; Fox, Amy; Buss, Kimberly A.
Purpose: The purpose of this translation study was to evaluate the feasibility and effectiveness of an adapted Group Lifestyle Balance (GLB) intervention for weight management implemented through an existing diabetes education program within a large health care delivery system for overweight/obese individuals with diabetes, prediabetes, or neither condition. Methods: Adults with BMI ≥ 25 kg/m 2 participated in an adapted GLB intervention designed to be appropriate regardless of diabetes status. Effectiveness was based on changes in weight and minutes of physical activity between baseline and completion of the 12-week core. Differences between subjects based on diabetes status were also examined. Results: A total of 111 subjects with diabetes, prediabetes, and no diabetes completed baseline survey data and attended at least 9 of the 12 core sessions from April 2010 through December 2011. All achieved significant weight loss, and the proportion of subjects who reported exercising at least 150 minutes/week increased. Conclusions: The adapted GLB intervention for weight management implemented through an existing diabetes education program in a large health care system was feasible and effective in the population, regardless of participants' diabetes status.